Historical land use and land-use change in Great Britain 1930s-2007 - Suggitt, Andrew J.; Wheatley, Christopher J.; Aucott, Paula; Beale, Colin M.; Fox, Richard; Hill, Jane K.; Isaac, Nick J. B.; Martay, Blaise; Southall, Humphrey; Thomas, Chris D.; Walker, Kevin J.; Auffret, Alistair G. (Swedish University of Agricultural Sciences, 2023)
This dataset contains summary data regarding historical (1930s-40s) land use and land-use change between 1930s and 2007 according to broad land-use categories. Data provided are summary values at the 10-km grid square 'hectad' level of the British National Grid, specifying the proportion and proportion of change in broad land-use categories.

Historical data are based on the first Land Utilisation Survey of Great Britain (Stamp 1931). For England and Wales, digitisation of the historical maps contains information supplied by Natural England, based on methods developed by Baily et al. (2011). For Scotland, map images were digitised using the R package HistMapR (Auffret et al. 2017). Both methods involve processing and classifying images based on the colour of the historical land-use map categories. Classified maps were then resampled to the 25m resolution of the modern UK Land Cover Map 2007 (Morton et al. 2011), and both historical and modern land-use categories were adjusted to produce broad categories of equivalent land use: Arable, Grassland, Urban, Woodland, Agriculturally-Improved Grassland and Surface Water. In Scotland, surface water from a modern map is used for the historical time period due to issues in classifying this category. Pixels within a 75m buffer of the modern road network were removed due to the disproportionate size of roads shown in the historical maps, and pixels falling into some coastal land-use categories in the modern maps were removed due to a lack of equivalent in the historical maps. The proportions of remaining pixels within each hectad, and the change in the proportion over time was then calculated. Full details of data creation and processing can be found in Suggitt et al. (2023), and more information on the data files can be found in the readme.

The extent of the data files:
GB_LandUseChange_Data.csv - table containing summary data, 2802 rows and 15 columns
GB_LandUseChange_LowlandGrasslandChange.csv - table containing data on lowland grassland change, 2802 rows and 10 columns

The file GB_LandUseChange_Raster.tif is a GeoTIFF file primarily intended to be used with the R script. It can also be opened using other GIS software.

If R is installed with required packages (see sessionInfo.txt), the file Rplots.pdf can be generated running:
Rscript GB_LandUseChange_Code.R

References:

Auffret, A.G., Kimberley, A., Plue, J., Skånes, H., Jakobsson, S., Waldén, E., Wennbom, M., Wood, H., Bullock, J.M., Cousins, S.A.O., Gartz, M., Hooftman, D.A.P., Tränk, L., 2017, HistMapR: Rapid digitization of historical land-use maps in R, Methods in Ecology and Evolution 8: 1453-1457. https://doi.org/10.1111/2041-210X.12788

Baily, B., Riley, M., Aucott, P. & Southall, H., 2011, Extracting digital data from the First Land Utilisation Survey of Great Britain – Methods, issues and potential, Applied Geography 31: 959-968. https://doi.org/10.1016/j.apgeog.2010.12.007

Morton, D., Rowland, C., Wood, C., Meek, L., Marston, C., Smith, G., Wadsworth, R., Simpson, I.C., 2011, Final Report for LCM2007 – the new UK Land Cover Map, Centre for Ecology & Hydrology, Wallingford, UK. http://nora.nerc.ac.uk/id/eprint/14854

Stamp, D.L., 1931, The Land Utilisation Survey of Britain. Geographical Journal 78: 40-47. https://doi.org/10.2307/1784994

Suggitt, A.J., Wheatley, C.J., Aucott, P., Beale, C.M., Fox, R., Hill, J.K., Isaac, N.J.B., Martay, B., Southall, H., Thomas, C.D., Walker, K.J., Auffret, A.G., 2023, Linking climate warming and land conversion to species’ range changes across Great Britain, Nature Communications, https://doi.org/10.1038/s41467-023-42475-0

Data avser historisk markanvändning och markanvändningsförändringar mellan 1930-40-talet och 2007 i Storbritannien. Data finns som andel av en 10km ruta av den brittiska rutnätet. Mer detaljer finns i den engelska beskrivningen, readme-filen samt följande publikationen:

Suggitt, A.J., Wheatley, C.J., Aucott, P., Beale, C.M., Fox, R., Hill, J.K., Isaac, N.J.B., Martay, B., Southall, H., Thomas, C.D., Walker, K.J., Auffret, A.G., 2023, Linking climate warming and land conversion to species’ range changes across Great Britain, Nature Communications, https://doi.org/10.1038/s41467-023-42475-0
Historical land use and land-use change in Great Britain 1930s-2007
Keywords: habitat mapping; land cover mapping; Habitats and biotopes; Naturtyper och biotoper; historical maps; historiska kartor; land use; markanvändning; land cover; landtäcke; Environmental Sciences; Miljövetenskap; Physical Geography; Naturgeografi; Ecology; Ekologi; Environment; Miljö